The Role of Islamic Education in Minimizing Lack of Discipline Behavior for Students - Hasibuan, Ahmad Ibrahim (MODELING: Jurnal Program Studi PGMI, 2023)
The research entitled "The Role of Islamic Education in Minimizing Undisciplined Behavior for Students" aims to 1) To know and understand the meaning and causes of undisciplined behavior, 2) To know and understand the efforts of schools and teachers in dealing with undisciplined behavior, and 3 ) To know and understand Islamic views on undisciplined behavior. This research uses literature study techniques from various existing studies in which researchers explain the role of Islamic education in minimizing undisciplined behavior for students. Literature study is an activity to search for some theories from several references that are relevant to the topic of discussion or problem that the author has found. The results in this research are; 1) Undisciplined behavior is behavior that violates disciplinary rules. And the causes of undisciplined behavior at school are divided into two groups, namely: a) Internal factors, namely factors that arise from the individual himself. In this case, both teachers and students. And b) External factors, namely factors that arise from community support or the situation and conditions of the school. 2) One way that the school can help students to improve discipline at school is by formulating and implementing a personal guidance program. And 3) Discipline is very important in Islamic teachings. It can even be said that Islam is a disciplined religion. Almost all religious services in Islam contain elements of teaching and disciplinary training.